The effect of inhaling thinner and/or cigarette smoke on rat kidneys - Cobanoglu, Bengu; Ozercan, Ibrahim H.; Ozercan, M. Resat; Yalcin, Orhan (Taylor & Francis Inc, 2007)
Although the effects of cigarette smoking and/or thinner inhalation on various organs have been investigated, there isn't enough study available in literature about their effects on kidneys. Therefore, in this study we investigated the effect of smoking and/or inhalation on the rat kidney. In this study, stand-alone inhalation of thinner and cigarette smoke and their application together were used to determine histopathologic changes, primarily the influences on rat kidneys. The study included 60 Wistar Albino species male rats. The 60 rats were divided into 4 groups of 15 rats each. Of the groups, three were working groups and the fourth was the control group. The rats in the first study group inhaled thinner only (T), those in the second group cigarette smoke only (CS), and the rats in the third group were made to inhale both thinner and cigarette smoke (TC). Each study group was divided into 3 subgroups each comprising 5 rats and inhalation was continued for periods of 2 wk, 4 wk, and 6 wk. Thinner was vaporized into the cage with a millipore pump at a constant pressure twice per day for 1 h for 5 days (toluene 2800-3000 ppm, acetone 500-600 ppm, isobutyl acetate 7000-8000 ppm, and isobutanol 6000-7000 ppm). Cigarette smoke was given 4 times per day for 15 min each, using a mechanism prepared with an aquarium motor (containing 1.2 mg nicotine, 13 mg tar, and 13 mg carbonmonoxide; 60 puffs/min). After that, rat kidneys were removed. The kidneys were weighed and were given macroscopic and microscopic examination. There were significant differences for the thinner and thinner + cigarette smoke groups in comparison to the control group, observed in both proximal and distal tubules. However, changes in the cigarette smoke group were only in proximal tubules and were smaller in extent. Thinner has been widely used as a industrial substance. Thinner usage is an important health problem. Those sniffing thinner generally also use cigarettes. The findings of the present study reemphasize the importance of taking immediate measures in order to prevent thinner inhaling among homeless children, who pose an important social problem, and to protect people who work in industrial branches that widely use thinner.
Keywords: Solvent Abuse; Inhalation; Intoxication; Toxicology; Toluene